Integrating Physical Activity into Lifestyle Management of Cardiovascular Disease - Bhat, Neeti; Mahotra, Narayan Bahadur; Gurung, Sanyukta; Dhital, Bidhi (Journal of Karnali Academy of Health Sciences, 2023)
The prevalence of cardiovascular diseases has almost doubled in Nepal from 1990 to 2019, making it the leading cause of death in the country. Despite numerous theories and experiments, satisfactory health outcomes have not been achieved. A holistic approach to lifestyle management is necessary to address the burden of cardiovascular disease. The Center for Disease Control recommends physical activity as a means of lifestyle modification, which can help reduce the risk of cardiovascular disease morbidity and mortality. Using the Metabolic Equivalent, physical activity can be quantified and prescribed based on frequency, intensity, time, type, and progression. Physicians can motivate patients, include physical activity in treatment plans, and refer patients to evidence-based exercise programs by qualified exercise professionals. In addition to individual interventions by physicians, the government should develop and enforce policies aimed at increasing physical activity. This review provides an overview of how physical activity can be integrated into lifestyle medicine to reduce the burden of cardiovascular disease.